Rekonstruksi Praktik Pembelajaran Berpusat pada Manusia di Era Artificial Intelligence - Zulfahreza; Jusniati H; Theopilus C. Motoh; Subhan Abdullah; Hasan Basri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The rapid development of Artificial Intelligence (AI) has transformed learning practices by improving access to information, enabling personalized learning, and enhancing educational efficiency. At the same time, it has introduced challenges related to the development of critical thinking, creativity, academic integrity, and the quality of pedagogical interactions. This study aims to reconstruct Human-Centered Learning practices in the era of Artificial Intelligence through a conceptual synthesis of relevant scholarly literature. The study employed a Systematic Narrative Literature Review (SNLR) approach within a library research design. Data were collected from five peer-reviewed journal articles selected purposively based on their relevance to Artificial Intelligence, Human-Centered Learning, humanistic learning, character education, and Deep Learning. The data were analyzed using thematic analysis involving data reduction, coding, categorization, and conceptual synthesis. The findings reveal that the reconstruction of learning practices is built upon five interrelated dimensions: learning objectives, teachers' roles, students' roles, learning strategies, and assessment. These dimensions constitute a Human-Centered Learning Reconstruction Model in the Era of Artificial Intelligence, positioning AI as a learning enabler while maintaining Human-Centered Learning as the guiding paradigm for fostering critical thinking, creativity, character development, and students' responsibility. This study contributes a comprehensive conceptual framework that integrates perspectives on Artificial Intelligence, humanistic learning, character education, and Deep Learning to support the development of adaptive, innovative, and human-centered learning practices.